The Effect of Ferric Oxide on Candida albicans - Nasif, Rima M.Y.; Rasheed, Hassan Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The biosynthesis of nanoparticle-mediated pigments has been widely used as an antimicrobial agent against microorganisms.In order to study the effect of ferric oxide (Fe2O3) nanoparticles on Candida albicans, they were biosynthesized by using pyocyanin pigment produced from Pseudomonas aeruginosa. Fe2O3NPs were characterized by using atomic force microscopy (AFM), Fourier transform-infrared spectroscopy (FTIR), Field Emission Scanning Electron Microscope (FE-SEM), Energy Dispersive X-ray Spectroscopy (EDX), and UV-Visible spectroscopy. From December 2022 to July 2023, a total of 48 samples of C. albicans were collected from burns, wounds, and urine from private labs and Al-Kindy hospital; only 19 were identified as C. albicans isolates according to the cultural and morphological characteristics and VITEK-2 system. For the antimicrobial effect, they were cultured on Mueller Hinton agar using the agar well diffusion method.The results provided evidence that the diameter of the inhibition zone was directly proportional to the concentration; at 0.1 μg/ml, the diameter of the inhibition zone was 30 mm, while at 0.0125 μg/ml, the diameter was 14 mm.The study confirms the concentration-dependent antifungal effect of Fe2O3 nanoparticles synthesized by biological methods, suggesting potential applications in antifungal therapy.